Bayt Al-Hikmah: Pusat Kebijaksanaan dan Warisan Ilmu Pengetahuan Islam dalam Peradaban Abad Pertengahan - Andy Riski Pratama; Salmi Wati; Rahmat Hidayat Hasan; Wilda Irsyad; Iswandi Iswandi (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
This article explores the role of Bayt Al-Hikmah as a monumental intellectual center during the Abbasid Dynasty. Built during the time of Caliph Abu Ja'far al-Mansur, this center developed into a famous library during the reign of Harun al-Rashid and Al-Ma'mun. It functions not only as a library, but also as an educational institution, astronomical observatory, and translation center, housing a collection of more than 60,000 books from various languages and regions. Important factors influencing the development of Bayt Al-Hikmah included the caliph's love of science, extensive translation activities, use of paper, the presence of scientists from various regions, material support, and enthusiasm for studying Islamic teachings. Despite achieving glory, the summary of the Abbasid dynasty started from internal political conflict to the Mongol attack which resulted in the fall of the city of Baghdad and the destruction of Bayt Al-Hikmah. Even though this intellectual center collapsed, the scientific legacy it produced remains a testament to the glory of science at that time, even though it experienced a tragic end.